Introduction pages, Notulae Scientia Biologicae 14(4), 2022 - Radu E. SESTRAS (Notulae Scientia Biologicae, 2022)
Notulae Scientia Biologicae (http://www.notulaebiologicae.ro), Issue 4, Volume 14, 2022: The papers published in this issue represent interesting novelties in different topics of life science. Among the exciting research or reviews, we invite readers to find news about: Wastewater treatment using chitosan and its derivatives; Phymatotrichopsis root rot and its biological control in the pecan tree in Mexico; The use of plants in the traditional treatment of diabetes patients – survey in southern Morocco; GA3 mediated enhanced transcriptional rate and mRNA stability of 3-hydroxy-3-methylglutaryl coenzyme a reductase 1 (NtHMGR1) in Nicotiana tabacum L.; Silicon alleviates PEG-induced osmotic stress in finger millet by regulating membrane damage, osmolytes, and antioxidant defense; UV-mediated enhancement of antibacterial secondary metabolites in endophytic Lasiodiplodia theobromae; Parametric and kinetic modeling, chemical composition, and comparative analyses of Algerian Mentha pulegium L. essential oil extracted from flowers and leaves by hydrodistillation; Introgression progress for phenotypic traits and parent-progeny diversity at advanced segregation population from Oryza barthii and O. glaberrima/O. sativa crosses.